Host Specificity in Raiding Behavior of the Slave-Making Ant Polyergus Lucidus - Linda Goodloe; Raymond Sanwald; Howard Topoff (Psyche: A Journal of Entomology)
In the pine barrens of Suffolk County, New York, at least three species of Formica (subgenus Neoformica) are used as slaves by the obligatory slave-making ant Polyergus lucidus. In any single nest, however, only one slave species may be found. This contrasts with the sympatric, facultative slave-making ants of the genus Formica (subgenus Raptiformica) in which single colonies often contain two or more species of slaves. The slave species exclusivity of P. lucidus might result in two ways: (1) raids could be made to only one slave species of the four available; or (2) raids could be made to more than one slave species, but the captured pupae could be consumed differentially by the resident slaves, favoring the survival to eclosion of only one slave species. This paper reports the results of a study demonstrating that colonies of P. lucidus will, if given a choice, raid only colonies of the slave species already present in the mixed nest. Since scouts typically lead nestmates to target Formica nests (Cool- Kwait & Topoff, 1984), this selective process must occur through the perceptions and actions of the scouts.